2022
DOI: 10.3390/toxins15010032
|View full text |Cite
|
Sign up to set email alerts
|

Charged Amino Acids Contribute to ZorO Toxicity

Abstract: Chromosomally encoded toxin-antitoxin systems have been increasingly identified and characterized across bacterial species over the past two decades. Overproduction of the toxin gene results in cell growth stasis or death for the producing cell, but co-expression of its antitoxin can repress the toxic effects. For the subcategory of type I toxin-antitoxin systems, many of the described toxin genes encode a small, hydrophobic protein with several charged residues distributed across the sequence of the toxic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This EAP region is required for robust translation but is also where the OrzO antitoxin binds. Multiple copies of the zor-orz locus from EDL933 or just the zorO-orzO pair increased the minimum inhibitory concentration of aminoglycoside antibiotics and reduced lag in sublethal levels of kanamycin, though the mechanism is unknown ( 9 , 26 ). We initially examined zor/orz sequence conservation with zorO/orzO from EDL933 as a query (depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This EAP region is required for robust translation but is also where the OrzO antitoxin binds. Multiple copies of the zor-orz locus from EDL933 or just the zorO-orzO pair increased the minimum inhibitory concentration of aminoglycoside antibiotics and reduced lag in sublethal levels of kanamycin, though the mechanism is unknown ( 9 , 26 ). We initially examined zor/orz sequence conservation with zorO/orzO from EDL933 as a query (depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The α-helical region appears to be critical for membrane interaction in most type I toxins, including Fst, TisB, IsbC, SprA1 and AapA1 ( Göbl et al, 2010 ; Mok et al, 2010 ; Steinbrecher et al, 2012 ; Solecki et al, 2015 ; Korkut et al, 2020 ). Additionally, specific charged amino acids in the predicted α-helical transmembrane domain are crucial for ZorO-mediated toxicity ( Bogati et al, 2022a ). We also found that the SprG1 31 sequence can be shortened to 25 amino acids with a minimum of 16 hydrophobic residues to retain toxicity, likely by maintaining the helix translocation across the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…These toxins also exhibit a membrane toxic effect, indicating the vital role of these basic C-terminal residues in the toxicity process. Moreover, charged amino acids in type I TA toxin protein ZorO are important for its toxicity and how it affects remain unknown [ 31 ]. Therefore, it is important to analyze the structural characteristics of AapA1-28 in the E. coli membrane and compare them with those of the AapA1 toxin protein.…”
Section: Discussionmentioning
confidence: 99%